Efektifitas Penerapan Metode Family-Centered Care terhadap Pasien Anak dengan Stress Hospitalisasi - Yeni Mila Wariantini Hadi; Zainal Munir; Wiwin Nur Siam (Ilmiah Institut Citra Internasional, 2020)
Parents do not understand and tend to entrust fully the healing of their children to nurses and doctors who handle them. The aim of the study was to determine the effectiveness of applying the Family Centered Care method to pediatric patients with stress hospitalization at the Prajekan Bondowoso Health Center. The pre-experimental one-group type pretest-posttest research design with a sample of 35 respondents with accidental sampling techniques. Then analyzed by paired t-test. The results of the study showed that after being treated the treatment had decreased, seen from the statistical test ρ value (0,000 <0,05). It was concluded that there was an effect of the application of the Family Centered Care method to pediatric patients with stress hospitalization at the Prajekan Bondowoso Health Center